The contribution of other effective areabased conservation measures (OECMs) to protecting global biodiversity - Jedediah, F. Brodie; Mairin C. M., Deith; Patrick, Burns; Scott J., Goetz; Charles, Cunningham; Jane K., Hill; Glen, Reynolds; Mohd Azlan, Jayasilan (Springer Nature Limited, 2025)
Nations recently agreed to set aside 30% of the planet by 2030 as conservation areas (the “30 × 30” goal) necessitating major expansions, not just of traditional protected areas like national parks, but also of ‘other effective areabased conservation measures’ (OECMs) – areas that provide de facto benefits to biodiversity despite conservation not being the primary management objective. But evidence for whether OECMs achieve positive biodiversity outcomes remains critically needed. Here we quantify how OECMs contribute to biodiversity conservation in the three high-biodiversity countries in which they have been extensively trialed. OECM performance varies across countries; those in South Africa align better with areas that a priori strategic planning identified as important for species conservation and key ecosystem services than those in Colombia and the Philippines. OECMs tend not to cover areas supporting regional connectivity in any of the countries. OECMs have potential to assist conservation, but policy, planning, and coordination at national and international levels would help ensure that new OECMs are strategically established and effectively managed to enhance outcomes for biodiversity conservation and ecosystem service provisioning.